Design and Assessment of System Architecture in Automatic System Transformation of E-Portfolio to E-Assessment through TOGAF and AHP - Wanotayapitak, Sukosol; Wannapiroon, Panita (Progress in Applied Science and Technology, 2018)
The main problem of E-Portfolio using is the assessment process that assessor have all done manually even though it is on the digital system, but even less leverage digital processing potentiality. This paper proposes the concept of automatic transformation from E-Portfolio to E-Assessment in the cloud as the form of information system architecture. However, the development of architecture still remains so many considerable issues such as cost effectiveness, future extensible of the system, system governance, and standard. Hence, solution finding for these issues is the first priority of all activities and from a literature review found that the TOGAF framework has appropriated properties to solve these issues. Therefore, this study uses TOGAF for designing by depict every process with picture in detail. Even if developed architecture is finished, but there are still has a problem of choosing the strategic information systems planning (SISP) to achieve the architecture implementation, so this paper proposes the analytic hierarchy process (AHP) to choose the appropriate choice of methodologies. The result of studies found the best choice of architecture implementation is strategic systems planning (SSP) methodology by the criteria of planning, documentation, programming, communication, governance, and stakeholder participation respectively.